Анализ результатов проведенных исследований в области химии перекисных соединений - Артемьев, С. Р.; Ватащук, П. Г.; Дворецкий, С. И.; Дворецкий, Д. С.; Шапорев, Валерий Павлович (НТУ "ХПИ", 2007)
У статті проведений загальний аналіз результатів досліджень, проведених російськими вченими в області хімії перекісних з'єднань у 19-20 ст. Показана актуальність використання отриманих результатів у сучасних умовах. Звернено увагу на важливість подальшого розвитку даного напрямку досліджень.

The general analysis of the researches conducted by the Russian scientists of 19-20 centuries in the field of peroxide chemistry and the results of their investigations were given in the article the topicality of modern practical implementation of the obtained results was shown. Special attention was paid to the important of further development of this approach of scientific research.
Keywords: перикись водорода; молекулярные соединения; полимеризация; окислы азота; регенеративные средства; термохимия